EFEKTIVITAS MODEL DIRECT LEARNING DAN STAD DITINJAU DARI PEMAHAMAN KONSEP MATEMATIS SISWA - wijaya, agung putra (Jurnal Pendidikan Progresif, 2016)
The Efectiveness of Direct Learning and STAD Model Viewed by Mathematical Conceptual Understanding of Students. This quasi experimental research was aimed to know the efectiveness of direct learning and STAD model viewed by mathematical conceptual understanding on field dependent students. The population of this research was all students of grade eight of SMPN 1 Natar Lampung Selatan. The sampling was done by cluster random sampling technique. This research used pretest-posttest control group design. The result of this research showed that on field dependent students, direct learning model was more effective than STAD model viewed by students’ mathematical conceptual understanding. Keywords: field dependent, conceptual understanding, direct learning, STAD DOI: http://dx.doi.org/10.23960/jpp.v6.i1.201601